2019
DOI: 10.1158/1078-0432.ccr-18-1904
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Stem Cell Apheresis is Feasible Post 131Iodine-Metaiodobenzylguanidine-Therapy in High-Risk Neuroblastoma, but Results in Delayed Platelet Reconstitution

Abstract: Purpose: Targeted radiotherapy with 131 iodine-metaiodobenzylguanidine ( 131 I-MIBG) is effective for neuroblastoma (NBL), although optimal scheduling during high-risk (HR) treatment is being investigated. We aimed to evaluate the feasibility of stem cell apheresis and study hematologic reconstitution after autologous stem cell transplantation (ASCT) in patients with HR-NBL treated with upfront 131 I-MIBG-therapy.Experimental Design: In two prospective multicenter cohort studies, newly diagnosed patients with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…With DLA, sufficient CTCs could be isolated to allow for diagnostic tests and tumor typing to be performed. As shown in our study and others, complications associated with DLA are mild and rare, making it an easily tolerable procedure even for NSCLC patients [39][40][41][42] The number of included patients in our study was relatively small and heterogeneous in stage and treatment line. However, previous studies have shown that the number of CTCs is not influenced by these patient characteristics, and any influence of patient characteristics is accounted for since the comparisons were performed for each patient in a matched manner.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…With DLA, sufficient CTCs could be isolated to allow for diagnostic tests and tumor typing to be performed. As shown in our study and others, complications associated with DLA are mild and rare, making it an easily tolerable procedure even for NSCLC patients [39][40][41][42] The number of included patients in our study was relatively small and heterogeneous in stage and treatment line. However, previous studies have shown that the number of CTCs is not influenced by these patient characteristics, and any influence of patient characteristics is accounted for since the comparisons were performed for each patient in a matched manner.…”
Section: Discussionmentioning
confidence: 81%
“…CTC detection has been increased by DLA in prostate and breast cancer patients before, but only small volumes of DLA product were processed [9][10][11]38]. DLA is a well-tolerable procedure, even in our NSCLC population, and has few complications, while placing minimal burden (only two hours of time) on patients [39][40][41][42]. Also the calculated efficacy of our procedures in isolating mononuclear cells (MNCs) was shown to be comparable with that of isolating stem cells, and DLAs in breast cancer patients [8][9][10][11]43].…”
Section: Discussionmentioning
confidence: 99%
“…origin [27]. Apheresis is known to be a tolerable procedure [28][29][30][31][32]. Recently, DLA was shown to increase CTC detection in prostate and breast cancer, even when patients had early-stage disease [10][11][12]27].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that megakaryocytes are capable of selective MIBG uptake may explain these findings. Our group described earlier that peripheral blood stem cell (PBSC) apheresis is feasible after upfront 131 I-MIBG therapy in neuroblastoma patients, although delayed platelet reconstitution occurred after reinfusion in MIBG-treated patients in comparison with chemotherapy-only-treated patients [ 42 ]. Interestingly, no association was found between bone marrow tumor infiltration at diagnosis and platelet reconstitution.…”
Section: Discussionmentioning
confidence: 99%